Sudan : 2014 article IV consultation and second review under the staff-monitored program - staff report ; press releases ; and statement by the Executive Director for Sudan. (IMF country report ;, 2014)
KEY ISSUESContext: Sudan's economy has yet to recover from the shock of South Sudan's secession three years ago, which took away three-quarters of oil production, half of its fiscal revenues, and two-thirds of its international payments capacity. Despite progress in implementing policies to address the resulting imbalances, inflation remains high and growth sluggish. Macroeconomic adjustment has been complicated by structural weaknesses, a heavy debt burden, U.S. sanctions, and volatile domestic and regional political factors. The authorities embarked earlier this year on a stabilization progr.